2007
DOI: 10.1210/jc.2007-0326
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Measurement in Wash-Out Fluid from Fine Needle Aspiration of Neck Masses in Patients with Primary and Metastatic Medullary Thyroid Carcinoma

Abstract: Objective: The aim of the study was to evaluate the usefulness of calcitonin (CT) assay in fine-needle aspiration biopsy (FNAB) washout fluid alone or combined with cytology in the presurgical study of medullary thyroid carcinoma (MTC) patients with thyroid nodules (TNs) and of suspicious neck MTC recurrences/metastases. Subjects and Methods:A total of 36 ultrasound-guided FNABs were performed in neck masses from 23 patients with borderline or high basal and pentagastrin-stimulated serum CT. Cytology and CT-FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
3
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 13 publications
8
114
3
9
Order By: Relevance
“…Boi et al (2007) recommend performing calcitonin measurements in wash-out fluids from fine needle aspiration to improve the diagnosis in primary and metastatic medullary thyroid carcinoma in the work-up thyroid nodules to prevent 'unnecessary' surgery. However, even this modification with fine needle aspiration evaluation may be inconclusive in 'calcitonin screened' patients, because medullary thyroid cancers measured from 0.7 to 7 mm in the group of patients with 'mildly elevated calcitonin levels'.…”
Section: Scheuba Et Al: Sporadic Hypercalcitoninemia Consequencesmentioning
confidence: 99%
“…Boi et al (2007) recommend performing calcitonin measurements in wash-out fluids from fine needle aspiration to improve the diagnosis in primary and metastatic medullary thyroid carcinoma in the work-up thyroid nodules to prevent 'unnecessary' surgery. However, even this modification with fine needle aspiration evaluation may be inconclusive in 'calcitonin screened' patients, because medullary thyroid cancers measured from 0.7 to 7 mm in the group of patients with 'mildly elevated calcitonin levels'.…”
Section: Scheuba Et Al: Sporadic Hypercalcitoninemia Consequencesmentioning
confidence: 99%
“…Although the number of patients was relatively small (27 individuals), these authors concluded that this procedure does not increase fineneedle aspiration's diagnostic value and that its value is considerably lower than determination of PTH in cystic nodes or thyroglobulin in lymph nodes. Consequently, in spite of other studies' findings (70,71), these authors do not recommend measuring calcitonin in thyroid aspirate as a routine method. It is obviously necessary to examine the value of this procedure in larger series and multicentric studies, since it is not possible to collect a sufficient number of samples in one center because of a relatively small prevalence of medullary carcinoma.…”
Section: Calcitonin Determination In Fine-needle Biopsy Aspiratementioning
confidence: 88%
“…The measurement of calcitonin in the washout fluid has been recommended to improve the diagnostic sensitivity of FNAB for MTC (22,23) (B/C). In a recent retrospective study, the cytology detected MTC in 21/37 lesions with 56.8% sensitivity whereas the measurement of calcitonin in the washout fluid showed sensitivity and specificity rates of 100% using a cutoff of 36 pg/mL (24) (B).…”
Section: (B)mentioning
confidence: 99%